INFORMATIONAL-ANALYTICAL COMPETENCE OF THE MANAGERS: VALUE IN PROFESSIONAL ADMINISTRATIVE ACTIVITY AND PRE-CONDITION OF IT’S FORMATION IN HIGH SCHOOLS - Nataliia A. Zinchuk (Інформаційні технології і засоби навчання, 2010)
In the article the analysis of theoretical sources concerning the significance of information - analytical competence formation by the future specialists on management as well as the situation with the formation process of it’s motivation are considered.